Annual Changes in the Ecological Environment and Microbial Community Structure and Their Correlation Analyses in the Core Area of Dalian National Sea Cucumber Stock Field of China - Xiaotong ZHU; Xiaojun RONG; Bin LI; Yingeng WANG; Jianlong GE; Meijie LIAO; Jinjin WANG; Yanqiang WU; Xintao ZHAO; Guojun SHI (Progress in Fishery Sciences)
Aquatic stock is the basis of cultivation of good strains and the core of biodiversity conservation. To comprehensively grasp of the core Breed Conservation area of China's first national sea cucumber native species farm, this study conducted an annual survey of the water body and sediment environment of the core breed conservation area from July 2022 to May 2023. Simultaneously, the annual change in microbial community structure in seawater and sediment was analyzed using high-throughput sequencing, and the correlation between ecological environment quality and microbial community structure was further completed. The results showed that the water quality of seawater was good, except for the reactive phosphate content in spring and the lead content in summer, autumn, and winter, which reached the water quality standard of ClassⅡand the heavy metal nickel, which met the water quality standard of ClassⅡin autumn. All other water quality indices met the water quality standard of ClassⅠ and the water body of the Breed Conservation area belongs to the poor trophic level. In the sediments, except for the chromium content in autumn which did not reach the standard of ClassⅠ, all other indices met the standard of ClassⅠ, indicating that the ecological environment of the core area is good. The results of microbial community structure analysis of seawater and sediments in four seasons showed that 3 796 OTUs were obtained in the water body of the core area and the Shannon index of the water body in the four seasons ranged from 5.90±0.04 to 6.84±0.01, with the highest in autumn and the lowest in summer; 4 151 OTUs were obtained in the sediment, and the Shannon index of the sediment in the four seasons was between 6.06±1.44 and 7.88±0.22, with the highest in summer and the lowest in spring. PcoA showed that the microbial community structure of the water body and sediments differed in the four seasons and the microbial community structure of the water body varied more by seasonal influences than that of sediments. The results of LEfSe analyses of water and sediment flora in different seasons showed that 73 and 66 significantly different bacteria were screened in water and sediment samples in different seasons, respectively (P < 0.05), among which the representative bacteria in the winter sediment contained Vibrionaceae and Psychromonadaceae, which highlights the potential threat of vibrio to the health of sea cucumber in winter. The correlation analysis between environmental factors and microbial community structure showed that temperature, pH, and salinity were the major environmental factors affecting the microbial community structure in the water body, whereas organic carbon, sulfide, heavy metal copper, and lead were the chief environmental factors affecting the microbial community structure in the sediments. These results provide support for assessing the ecological environment of the core area for Breed Conservation, analyzing its risk factors and influencing factors, and providing scientific basis for the efficient preservation of the native sea cucumber in China.